Effect Of Compensation And Work Environment On Employee Job Satisfaction At Pt. Pg Rajawali Ii Unit Jatitujuh Majalengka - Ega Yohananda Agustin; Sandi Nasrudin Wibowo (Universitas Muhammadiyah Jember, 2021)
This study aims to analyze the effect of compensation and work environment on employee job satisfaction at PT. PG Rajawali II Unit Jati Tujuh Majalengka with a total sample of 64 employees. quantitative, which aims to determine the effect of two or more variables. The analysis technique used is multiple regression and hypothesis testing using t statistical tests to test the partial regression coefficients and f statistical tests to test the effect together with a level of significance of 5%. The variables in this study are Compensation (X1), Work Environment (X2), and Employee Job Satisfaction (Y). Data analysis using SPSS 21.0 for windows program. The results of this study indicate that there is a significant influence between compensation on job satisfaction of employees at PT. PG Rajawali II Unit Jati Tujuh, with a value of tcount ttable 6, 463 1.9989. There is a significant influence between the work environment and employee job satisfaction at PT. PG Rajawali II Unit Jati Tujuh, with a value of tcount ttable 2.109 1.9989. And there is a significant effect between compensation and work environment together on job satisfaction of employees of PT. PG Rajawali II Unit Jati Tujuh, this is obtained with a value of Fcount Ftable, which is 33,639 3.15.